Comparative and evolutionary genomics of angiosperm trees - Groover, Andrew Thomas ; Cronk, Quentin C. B. (Springer, 2020)
Preface -- Paleobotanical origins and diversification of angiosperm trees -- Diversification of angiosperm trees -- Secondary woodiness -- Salient features and variation in angiosperm wood anatomy and physiology -- Populous -- Eucalyptus -- Emerging genomics of angiosperm trees -- Structural genomics, genome duplications/ploidy, repeat sequences -- Evolutionary histories of gene families -- Population genomics, mating systems, gender determination -- Speciation and hybridization -- Perennial growth, form and architecture -- Wood development and chemistry -- Phenology, maturation and flowering -- Abiotic stress -- Ecological and landscape genomics -- Pathogen, insect, and symbiotic interactions -- Index.